Hydrothermal Synthesis of Lanthanum-Doped MgAl-Layered Double Hydroxide/Graphene Oxide Hybrid and Its Application as Flame Retardant for Thermoplastic Polyurethane - Yi Qian; Peng Qiao; Long Li; Haoyue Han; Haiming Zhang; Guozhang Chang (Advances in Polymer Technology)
A novel lanthanum-doped MgAl-layered double hydroxide/graphene oxide hybrid (La LDH/GO) with a La3+/Al3+ molar ratio of 0.05 was successfully synthesized by the hydrothermal method. The structure and morphology of as-prepared samples were characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and transmission electron microscopy (TEM). Then, La LDH/GO was added into thermoplastic polyurethane (TPU) to investigate its effect on flame retardancy, smoke suppression, and thermal stability of TPU composites. The cone calorimeter test (CCT) results indicated that the peak heat release rate (PHRR) and peak smoke production rate (PSPR) values of TPU with La LDH/GO decreased by 33.1% and 51% compared with neat TPU, respectively. Therefore, La LDH/GO can play a good role in flame retardancy and smoke suppression of TPU matrix during combustion. In the meantime, La LDH/GO could improve the char yield of TPU composites, which is attributed to the interaction between the physical barrier effect of GO and the catalytic effect of 0.05 La LDH.